Tog on software design - Tognazzini, Bruce (Addison-Wesley Pub. Co., 1996)
Tog on Software Design discusses the evolution computers will undergo in the coming decade and the impact these changes will have on society as a whole. You'll find essays on topics from quality management to the meaning of standards, to corporate structure and cooperation, interspersed with responses to queries supplied by designers and developers. These essays will furnish industry managers, programmers, and designers with a blueprint for success in the coming decade. Discussion of issues surrounding home, school, and business will give computer enthusiasts a fascinating view of how their lives will soon be transformed.